본태성 고혈압에 대한 杞菊地黄丸의 효과에 관한 체계적 고찰 및 메타 분석 - 한인식(In Sik Han); 신지혜(Ji Hye Shin); 조윤영(Yoon Young Cho); 박해모(Hae Mo Park); 양창섭(Chang Sop Yang); 정민정(Min Jeong Jeong); 장인수(Insoo Jang); 선승호(Seung Ho Sun) (동의생리병리학회지, 2017)
The purpose of this study is to investigate the blood pressure reducing effect of Qi-Ju-Di-Huang-Wan (QJDHW) in adults with essential hypertension by using methods of systemic review and meta-analysis. Major search engines, such as PubMed, EMBASE, Cochrane library, Web of Science, CNKI, CiNii, J-STAGE, KISS, NDSL, RISS, OASIS, DBpia and so on, were used. The search period we used is from the start date of the search engine to October 30, 2016 and no language limits were placed. Randomized controlled trials using QJDHW in adults with essential hypertension were searched and extracted by two independent researchers. Meta-analysis was performed on outcome variables of the total effective rate (TER), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Risk of bias (RoB) of Cochrane was used to assess methodological quality. Thirteen studies were finally selected. We observed that the combined treatment of QJDHW and antihypertensive drug had 3.6 times the odds ratio of TER for blood pressure lowering than a single use of an antihypertensive drug. Additionally, mean differences of SBP and DBP were -8.88 mmHg (95% Confidential Interval (CI) -12.77 mmHg, -5.00 mmHg, P<0.00001), -7.09 mmHg (95% CI -9.93, -4.25, P <0.00001), respectively. Single use of QJDHW did not reduce blood pressure more than an antihypertensive drug. All items of RoB were unclear and the methodological quality was low. Our analysis suggests that the combination of QJDHW and antihypertensive drugs may be more effective in reducing blood pressure than a single antihypertensive drug. But due to low methodological quality, careful interpretation will be needed and systematic long-term clinical trials will be required. KCI Citation Count: 6